THE DEVELOPMENT OF THE BANKING INDUSTRY IN THE DIGITAL ERA IN INDONESIA - Dadi Kuswandi; Sri Wulan Windu Ratih; Radi Sahara; Widiarsih Widiarsih; Bambang Gunawan H (LPPM STIE Muhammadiah Bandung, 2022)
The banking industry has experienced an increase in the services that customers can provide due to the emergence of the industrial revolution 4.0, so it has become more innovative. Using this information technology provides innovation in the form of digitizing the banking sector from various sides. This research aims to see how developments occur in the Indonesian banking industry, which has begun to be digitized. This research will be carried out using a qualitative approach and literature study methods. The data obtained came from various research results that discussed the digitalization of the banking sector that occurred in Indonesia. This study found that industries that want to survive need to adopt new technologies to stay ahead or stick with existing conventional systems and then slowly disappear.